2016
DOI: 10.4025/actascianimsci.v38i2.29858
|View full text |Cite
|
Sign up to set email alerts
|

<b>Productivity of japanese quails in relation to body weight at the end of the rearing phase

Abstract: ABSTRACT. Two experiments were conducted at different times with the objective of investigating how the body weight of Japanese quails at the end of the rearing period may alter the performance during the laying phase. In both experiments, the birds were distributed in five treatments according to their body weights, which were obtained at 42 and 35 days of age for the first and second experiments respectively, and the following categories were considered for said experiments: very light, light, average, heavy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The highly significant difference in body weight between the selected lines is in accordance with the earlier reports ( Vieira Filho et al, 2016 ; Dzuriatmono et al, 2019 ). The mean body weight at seventh week observed in the current study (266.87 g) was higher than the value of 244.10 g by Lofti et al (2012) .…”
Section: Discussionsupporting
confidence: 92%
“…The highly significant difference in body weight between the selected lines is in accordance with the earlier reports ( Vieira Filho et al, 2016 ; Dzuriatmono et al, 2019 ). The mean body weight at seventh week observed in the current study (266.87 g) was higher than the value of 244.10 g by Lofti et al (2012) .…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, our results are in agreement with the results of Sauveur (1988) who reports that the start of laying in Japanese quail is between 6 and 7 weeks of age. According to Vieria Filho et al (2016), the sexual maturity of Japanese quail can be influenced by genetic factors and body weight, which is why quails of the SF10 group (with 220g of weight) have an earlier sexual maturity in comparison with other groups. However, the addition of sunflower oil 10% in the diet improves the weight gain of quails.…”
Section: Growth and Laying Performancesmentioning
confidence: 99%
“…In spite of the apparent illogical nature of these findings, a similar relationship was also noted in some former studies. For example, Vieira Filho et al [35] demonstrated that, while laying phase productivity of Japanese quails was considerably decreased when their body weight was less than 140 g at 42 days of age or less than 120 g at 35 days of age, egg production (i.e., the number of eggs laid during the laying period) in light and medium breeds was higher than that of heavy and very heavy breeds. Similar results were also obtained by Lukanov et al [36].…”
Section: Correlation Between Performance Traits and Morphometric Char...mentioning
confidence: 99%
“…Body measurements of quails by days(1,7,14,21,28,35, 42, 49, and 56) of their growth and their productivity indicators (mean value ± SD).…”
mentioning
confidence: 99%